Quality Control of The Internalization of Religious Maturity - Dyah Nur Uswatun Hasanah; Ridwan Basalamah; Eka Farida (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
This article analyzes the quality control model in inculcating the five soul values ​​owned by Pesantren Nurul Jadid Probolinggo so that students' religious maturity is formed and readiness to serve the nation and state. The research method used is qualitative, with the type of research being a multi-case study. Researchers collected data employing in-depth interviews, participant observation, and documentation. While data analysis with data presentation, data condensation, and concluding. As for checking the validity of the data, it is done by using credibility, transferability, dependability, and confirmability techniques. This study resulted in the findings: quality control of the internalization of religious and state maturity in the Nurul Jadid Islamic boarding school was carried out through the following model: guidance from teachers to students, worship with sincerity values ​​by instilling faith values ​​in the heart, giving inspirational stories, able to organize life personal, able to recognize good and bad, create a conducive environment through various organizational media.